2018
DOI: 10.1089/jwh.2017.6806
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Serum 25-Hydroxyvitamin D Are Related to Improved Glucose Homeostasis in Women with Postmenopausal Osteoporosis

Abstract: Our results support the hypothesis that circulating 25(OH)D levels are related to improved glucose homeostasis in women with PMO. However, this relationship was apparent only in the presence of high circulating levels of 25(OH)D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…They proposed a target 25(OH)D of 50 ng/mL; higher than the levels previously suggested in other studies, in the attempt to influence and reduce the incidence rate of diabetes [36]. These data are consistent with the levels published recently by Avila-Rubio et al in postmenopausal women, the authors link values of 25(OH)D > 45 ng/dL in these women with better glycemic indexes measured by homeostasis model assessment (HOMA) [37].…”
Section: Vitamin D and Type 2 Diabetes (T2d)supporting
confidence: 87%
See 1 more Smart Citation
“…They proposed a target 25(OH)D of 50 ng/mL; higher than the levels previously suggested in other studies, in the attempt to influence and reduce the incidence rate of diabetes [36]. These data are consistent with the levels published recently by Avila-Rubio et al in postmenopausal women, the authors link values of 25(OH)D > 45 ng/dL in these women with better glycemic indexes measured by homeostasis model assessment (HOMA) [37].…”
Section: Vitamin D and Type 2 Diabetes (T2d)supporting
confidence: 87%
“…Von Horst et al found that optimal 25OHD concentrations for reducing IR were around 50 ng/dL in a randomized controlled study with 81 Asian women [49]. Avila Rubio et al [37], in a study conducted in women with postmenopausal osteoporosis, suggested that the established goal of reaching a level of 25(OH)D > 30 ng/mL was insufficient to improve glucose metabolism in these population. The data from this study indicates that 25(OH)D > 45 ng/mL are necessary to achieve this goal.…”
Section: Vitamin D and Type 2 Diabetes (T2d)mentioning
confidence: 99%
“…A 29-year prospective cohort study including 9841 participants, it was found higher risk for T2D development (OR: 1.5 95% CI 1.33-1.70) in the subjects with 25(OH)D levels in the lowest quartile (<5 ng/mL) compared to those in the highest quartile (≥20 ng/mL) [95]. The study of Avila-Rubio et al reported better glycaemia indices measured by the HOMA in postmenopausal women with 25(OH)D values > 45 ng/dL without established disturbances in glucose metabolism compared to those below [98]. These data are consistent with those of Park et al [99], showing an inverse dose-response association between 25(OH)D level and the diabetes risk.…”
Section: Vitamin D Status and T2dmentioning
confidence: 98%
“…However, the potential benefits of higher values to achieve extra-osseous benefits is a question currently under investigation [109]. Avila-Rubio et al suggested that the stated goal of achieving a 25(OH)D level > 30 ng/mL was insufficient to improve glucose metabolism in women with postmenopausal osteoporosis, proposing an optimal level of 45 ng/mL to achieve effects on these targets [98]. Von Horst et al reported an optimal 25(OH)D concentrations around 50 ng/mL for reducing insulin resistance in Asian women [110].…”
Section: Vitamin D Supplementation and T2dmentioning
confidence: 99%
“…Ei au propus o concentrație țintă pentru 25 (OH) D de 50 ng/ml, mult mai mare decât concentrațiile sugerate în alte studii, în încercarea de a influența și de a reduce rata apariției DZ [46]. Aceste date sunt în concordanță cu concentrațiile publicate de Avila-Rubio și colaboratorii la femeile aflate în postmenopauză, autorii observând că valori ale 25 (OH) D mai mari de 45 ng/dl la aceste femei se asociază cu indice glicemic bun [47].…”
Section: Roluri Fiziologice Ale Vitaminei Dunclassified